Efektivitas Sistem Pengelolaan Reklame dalam Mendukung Kualitas Kebijakan Penataan Ruang: Studi Kemitraan Yousee Company Dengan Pemerintah Kabupaten Karanganyar - Timotius Suryadi; Yitno Puguh Martomo; Ana Mayasari (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
Billboard management requires an accurate, integrated, and accessible information system to support evidence-based spatial planning policies. This study aims to analyze the effectiveness of the billboard management system implemented by Yousee Company and its contribution to the quality of spatial planning policies in Karanganyar Regency. The study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation. The informants included Yousee Company management, the Investment and One-Stop Integrated Services Office, the Public Works and Spatial Planning Office, and the Regional Finance Agency of Karanganyar Regency. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data collection, data condensation, data display, and conclusion drawing. The findings show that the billboard management system meets six indicators of information system effectiveness, namely accuracy, relevance, timeliness, efficiency, accessibility, and integrity. Accuracy is supported by GPS technology and geospatial mapping, while relevance is reflected in the alignment of data with licensing and spatial planning requirements. Timeliness is strengthened through automated notifications, whereas efficiency is demonstrated by reduced operational time and costs. Accessibility facilitates data exchange across government agencies, while integrity is maintained through audit trails and layered verification. Overall, the system contributes to improving spatial planning policies by providing valid, transparent, coordinated, and accountable data for decision-making and regulatory implementation.